Analisis Penambahan Aditif Boraks terhadap Compressive Strength dan Shear Bond Strength Semen Pemboran Kelas G - Kevin Patrick Kumambouw; Baiq Maulinda Ulfah; Dennies Marcelino Assa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes the effect of adding borax (sodium tetraborate) as a retarder additive on both parameters, using concentration variations of 0%, 0.25%, 0.5%, and 1% BWOC at a fixed water-cement ratio of 0.44. Testing was performed with a hydraulic press after 24 hours of curing. Compressive strength rose from 654.2 psi (0%) to 1,122.3 psi (0.25%) and peaked at 1,421.1 psi at 0.5%, before dropping sharply to 525.6 psi at 1%. Shear bond strength followed a similar pattern: 144.5 psi (0%), 233.6 psi (0.25%), 295.7 psi (0.5%, the highest value), and 127.3 psi at 1%. A concentration of 0.5% BWOC proved to be the optimum point, while excess borax triggered over-retardation that hindered C-S-H formation and reduced cement strength